IA1 microinvasive cervical adenocarcinoma in a young woman: conservative procedure and reproductive outcome - Tavares, Barbara; Teixeira, Círbia Silva Campos; Vale, Diama Bhadra do; Bragança, Joana Froes; Teixeira, Julio Cesar (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: The expansion of cytological screening programs for cervical cancer leads to an increase in the proportion of both adenocarcinomas and diagnoses in young women with reproductive intention. Conservative treatment is not fully established. Objective: to report the conservative management and follow-up difficulties of a real case of microinvasive cervical adenocarcinoma in a young woman. Case report: This is a case report of a 23-yearold patient with stage IA1 microinvasive cervical adenocarcinoma related to HPV18. The patient was vaccinated against HPV 16/18 at 16 years of age and conservatively treated. She became pregnant during follow-up with a favorable outcome. Conclusion: We discuss the difficulties and uncertainties regarding follow-up and opportunity for hysterectomy, emphasizing the need for a multidisciplinary approach to make a balanced decision between conservative treatment and oncological safety, as well as mitigate follow-up difficulties in real life.